“Do I Really Need a Course to Learn to Teach Students with Disabilities? I’ve Been Doing It for Years” - Sokal, Laura; Sharma, Umesh (Canadian Journal of Education/Revue canadienne de l'éducation, 2018)
A quantitative study was conducted to compare the attitudes, efficacy, and concerns about inclusive education within three groups of teachers in Manitoba, Canada (N = 191). The three groups included pre-service teachers with coursework about inclusive education, but limited experience in inclusive settings; in-service teachers with experiences in inclusive settings, but no coursework about inclusion; and in-service teachers with inclusive teaching experiences as well as coursework about inclusion. Analysis of variance revealed significant differences between the groups in all three dependent variables and supported the importance of coursework, even for experienced teachers. Subsequent regression analysis demonstrated that experiences and course work contributed differentially to the development of attitudes, concerns, and efficacy for inclusive teaching in pre-service and in-service teachers. Implications on both in-service and pre-service teacher education are discussed.